High-strength anti-freezing lightweight aggregate and preparation method thereof
By using high-strength anti-coagulant light aggregate prepared with high content of industrial solid waste, the problems of low strength and complex preparation process of existing anti-coagulant ice agents are solved, and efficient anti-coagulant ice effect and low-cost production are achieved. .
Patent Information
- Application Number
- CN202411556386.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-11
AI Technical Summary
In the treatment of road ice condensation in high-altitude areas, existing anti-coagulation agents have problems such as low aggregate strength, poor anti-coagulation properties, complex preparation processes and high raw material costs.
Prepare high-strength anti-coagulant light aggregates through raw materials with an industrial solid waste content of 70-90%, including industrial by-product gypsum, slag, steel slag, ultra-fine nano powder, composite cement, anti-coagulant and cold consolidation excitation The agents, etc. are prepared by mixing, stale, granulation and maintenance processes.
The preparation of high-strength anti-coagulant ice light aggregate is achieved, with the characteristics of high strength, light weight, good anti-icing effect, simple preparation process and low production cost.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic non-metallic materials, and more specifically relates to a high-strength anti-icing lightweight aggregate and a preparation method thereof. Background Art
[0002] Traffic jams frequently occur in cold regions due to road icing during the snowy season. Road icing not only reduces the road surface's anti-skid coefficient, seriously affecting traffic safety and traffic efficiency, but also easily causes damage such as frost heave, potholes, and cracks inside the concrete, shortening the service life of the concrete road. At present, anti-icing agents are mostly used for surface deicing, but this method has a short anti-icing cycle, low efficiency, and will also have adverse effects on the road surface and the surrounding environment.
[0003] The invention patent with application number 201010100920.2, "A porous salt-storing aggregate and its preparation method", proposes a porous salt-storing aggregate with a simple preparation process and low price, but it has the disadvantages of low aggregate strength, fast salt release rate and weak anti-icing effect in the later stage. The invention patent with application number 202410244534.2, "Slow-release anti-icing polyurethane mixture suitable for steel bridge deck and preparation method", proposes a polyurethane mixture with slow salt release and good anti-icing effect, but it has the problems of complex preparation process and high cost. The invention patent with application number 201811598188.9, "Anti-icing micro-surfacing maintenance material and preparation method", proposes an anti-icing micro-surfacing maintenance material with good compatibility with emulsified asphalt, but it has the disadvantages of small salt storage and limited anti-icing effect.
[0004] Therefore, it is of great significance to develop a lightweight aggregate for concrete with high strength, excellent anti-icing effect, simple preparation process and low raw material cost. Summary of the invention
[0005] The purpose of the present invention is to provide a high-strength anti-icing lightweight aggregate and a preparation method thereof. The high-strength anti-icing lightweight aggregate is prepared by raw materials with an industrial solid waste content of 70 to 90%, which can effectively solve the current problems of low aggregate strength, poor anti-icing properties, complex preparation process and high cost of raw materials used.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention is to provide a high-strength anti-ice light aggregate, which is prepared from raw materials including the following mass fractions:
[0008] 50-90 parts of industrial by-product gypsum, 10-30 parts of slag, 5-15 parts of steel slag, 10-30 parts of ultra-fine nano powder, 2-15 parts of composite cement, 2-10 parts of anti-icing agent, 0.5-3 parts of cold solidification activator, 0.2-2 parts of polyether modified silicone oil and 12-30 parts of water.
[0009] Preferably, the industrial by-product gypsum includes one or more of desulfurized gypsum, phosphogypsum, titanium gypsum and citric acid gypsum; the attached water content of the industrial by-product gypsum is ≤20wt%, and the dry basis CaSO4·2H2O content is ≥80wt%; the slag includes blast furnace slag powder; the specific surface area of the slag is ≥400m 2 / kg, 28d intensity activity index ≥95%, particle size 0.1~75μm.
[0010] More preferably, the industrial by-product gypsum is sieved before use, and the sieve under is used; the sieve used for sieving is a 200-mesh sieve.
[0011] Preferably, the steel slag comprises converter steel slag powder, and the converter steel slag powder is preferably a converter steel slag powder that has been subjected to heat-suffocating treatment; the specific surface area of the steel slag is ≥530m 2 / kg, 28d strength activity index ≥80%, f-CaO content ≤2%, particle size 0.1-76μm; the ultra-fine nano powder includes one or more of fly ash, silica powder, waste stone powder, ceramic polishing waste; the specific surface area of the ultra-fine nano powder is ≥750m 2 / kg, average sphericity ≥0.85, particle size 0.1~38μm.
[0012] Preferably, the composite cement is prepared by compounding silicate cement and sulphoaluminate cement, the mass ratio of silicate cement to sulphoaluminate cement is 9-12:1; the strength grade of silicate cement is ≥42.5; the strength grade of sulphoaluminate cement is ≥52.5.
[0013] The hydration product ettringite formed by the hydration of the sulphoaluminate cement in the composite cement of the present invention has a nucleus effect, which can promote the hydration reaction between industrial by-product gypsum, slag, steel slag and other industrial solid wastes, further accelerate the crystallization and growth of ettringite, and improve the strength and durability of aggregates.
[0014] Preferably, the anti-icing agent includes two or more of n-tetradecane, n-dodecane, n-undecane and n-decane.
[0015] The composite anti-icing agent of the present invention can be used to adjust the anti-icing temperature range and effect of concrete.
[0016] Preferably, the cold consolidation activator is prepared by compounding calcium chloride and triethanolamine, and the mass ratio of calcium chloride to triethanolamine is 9 to 15:1.
[0017] The mixing of the cold consolidation activator of the present invention can significantly promote the gelling and hydration of active components in the aggregate and improve the early strength of the material.
[0018] The reaction mechanism of the present invention is that in the alkaline environment provided by silicate cement, active components in industrial by-product gypsum, slag, steel slag and ultrafine nanopowder will undergo hydration reaction to form sulphoaluminate-based aggregates with ettringite as the main mineral component.
[0019] The anti-icing mechanism of the present invention is that the main anti-icing substance adsorbed in the high-strength anti-icing lightweight aggregate has the characteristics of hydrophobicity and low-temperature phase change. When the temperature drops below 0°C, the main anti-icing substance undergoes a phase change reaction, releases heat, and avoids ice formation inside and on the surface of the concrete.
[0020] The second technical solution of the present invention is to provide a method for preparing the high-strength anti-icing lightweight aggregate, comprising the following steps:
[0021] According to the raw material ratio of the high-strength anti-icing lightweight aggregate, industrial by-product gypsum, slag, steel slag, ultrafine nano powder, composite cement and anti-icing agent are mixed and aged, and after the aging, cold solidification activator, polyether modified silicon and water are added in sequence and mixed and granulated to obtain spherical blanks; the spherical blanks are cured to obtain the high-strength anti-icing lightweight aggregate.
[0022] Preferably, the mixing time is independently 2 to 30 minutes; the aging time is 24 to 48 hours.
[0023] More preferably, the aging is: wrapping with a film and placing for 24 to 48 hours.
[0024] Preferably, the particle size of the spherical blank is 0.125-9.5 mm.
[0025] Preferably, the curing includes a first curing and a second curing; the temperature of the first curing is 20-25°C, the relative humidity of the first curing is 90-98%, and the time of the first curing is 1-3 days; the second curing is curing in water or sodium sulfate solution, the temperature of the second curing is 20-40°C, and the time of the second curing is 7-14 days.
[0026] The present invention discloses the following technical effects:
[0027] 1. The industrial solid waste content in the high-strength anti-icing lightweight aggregate prepared by the present invention is 70-90%, which has the characteristics of high solid waste utilization rate and high added value.
[0028] 2. The present invention can prepare high-strength anti-ice light aggregate only through mixing, aging, granulation and curing processes, and has the characteristics of simple preparation process, convenient operation and low production cost.
[0029] 3. The cylinder compressive strength of the high-strength anti-icing light aggregate prepared by the present invention is 10-20 MPa, and the apparent density is 1400-1700 kg / m 3 The anti-icing temperature range is -25 to 0°C, and it has the characteristics of high strength, light weight and good anti-icing effect. DETAILED DESCRIPTION
[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0031] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0032] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0033] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0034] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0035] The performance tests of cylinder compressive strength, apparent density and anti-icing temperature of the lightweight aggregate described in the following examples and comparative examples are based on the following standards and methods: the cylinder compressive strength and apparent density of the lightweight aggregate are tested in accordance with "Lightweight Aggregate and Its Test Methods Part 2: Test Methods for Lightweight Aggregate" GB / T17431.2-1998; the anti-icing temperature is determined by observing the freezing of concrete, and the anti-icing temperature is tested using a differential scanning calorimeter.
[0036] The parameters of the raw materials used in the following examples and comparative examples are as follows:
[0037] The attached water content of industrial by-product gypsum is ≤20wt%, and the dry basis CaSO4·2H2O content is ≥80wt%; the industrial by-product gypsum is sieved with a 200-mesh sieve before use, and the sieve under is used;
[0038] The specific surface area of slag is ≥400m 2 / kg, 28d intensity activity index ≥95%;
[0039] The specific surface area of steel slag is ≥530m 2 / kg, 28d strength activity index ≥80%, f-CaO content ≤2%;
[0040] The specific surface area of ultrafine nanopowder is ≥750m 2 / kg, average sphericity ≥ 0.85;
[0041] The strength grade of silicate cement is ≥42.5; the strength grade of sulphoaluminate cement is ≥52.5.
[0042] Example 1
[0043] The raw materials and amounts used in this example are as follows:
[0044] 55 parts of desulfurized gypsum, 30 parts of blast furnace slag powder (particle size 75μm), 7.5 parts of heat-stewed converter slag powder (particle size 50μm), 15 parts of fly ash (particle size 38μm), 15 parts of composite cement (compounded by ordinary Portland cement with strength grade 42.5 and sulphoaluminate cement with strength grade 52.5 in a mass ratio of 10:1), 5 parts of n-tetradecane, 5 parts of n-undecane, 3 parts of cold consolidation activator (compounded by calcium chloride and triethanolamine in a mass ratio of 12:1), 0.6 parts of polyether modified silicone oil, and 10 parts of water;
[0045] The preparation method is as follows:
[0046] According to the above raw material proportions, desulfurized gypsum, blast furnace slag powder, hot-stewed converter slag powder, fly ash, composite cement, n-tetradecane and n-undecane are mixed in a mixer for 2 to 30 minutes until uniform; after aging for 48 hours, cold consolidation activator, polyether modified silicone oil and water are added thereto in sequence and mixed again for 2 to 6 minutes until uniform to obtain a mixture; the mixture is formed into spherical billets with a particle size of 0.125 to 9.5 mm by a ball-forming granulator; the spherical billets are first cured at a temperature of 25°C and a relative humidity of 95% for 3 days, and then cured in water at a temperature of 30°C for 12 days to obtain high-strength anti-icing lightweight aggregate.
[0047] After testing, the cylinder compressive strength of the high-strength anti-ice light aggregate obtained in this embodiment is 17.4MPa, and the apparent density is 1680kg / m 3 , the anti-freezing temperature is -7.4℃.
[0048] Example 2
[0049] The raw materials and amounts used in this example are as follows:
[0050] 65 parts of phosphogypsum, 25 parts of blast furnace slag powder (particle size 60μm), 10 parts of hot-stewed converter slag powder (particle size 60μm), 20 parts of silica powder (particle size 35μm), 12 parts of composite cement (compounded by ordinary Portland cement with strength grade 42.5 and sulphoaluminate cement with strength grade 52.5 in a mass ratio of 10:1), 4.8 parts of n-tetradecane, 3.2 parts of n-decane, 2.4 parts of cold consolidation activator (compounded by calcium chloride and triethanolamine in a mass ratio of 10:1), 1 part of polyether modified silicone oil, and 8.5 parts of water;
[0051] The preparation method is as follows:
[0052] According to the above raw material proportions, phosphogypsum, blast furnace slag powder, hot-stewed converter steel slag powder, silicon powder, composite cement, n-tetradecane and n-decane are mixed in a mixer for 2 to 30 minutes until uniform; after aging for 24 hours, cold consolidation activator, polyether modified silicone oil and water are added thereto in sequence and mixed again for 2 to 6 minutes until uniform to obtain a mixture; the mixture is formed into spherical billets with a particle size of 0.125 to 9.5 mm by a ball-forming granulator; the spherical billets are first cured at a temperature of 22°C and a relative humidity of 98% for 2 days, and then cured in a 5wt% sodium sulfate aqueous solution at a temperature of 35°C for 14 days to obtain high-strength anti-icing lightweight aggregate.
[0053] After testing, the cylinder compressive strength of the high-strength anti-ice light aggregate obtained in this embodiment is 17.2MPa, and the apparent density is 1545kg / m 3 , the anti-freezing temperature is -13.1℃.
[0054] Example 3
[0055] The raw materials and amounts used in this example are as follows:
[0056] 75 parts of titanium gypsum, 20 parts of blast furnace slag powder (particle size 60μm), 12.5 parts of hot-stewed converter slag powder (particle size 40μm), 20 parts of waste stone powder (particle size 20μm), 9 parts of composite cement (compounded by ordinary Portland cement with strength grade 42.5 and sulphoaluminate cement with strength grade 52.5 in a mass ratio of 11:1), 1.2 parts of n-dodecane, 4.8 parts of n-decane, 1.8 parts of cold consolidation activator (compounded by calcium chloride and triethanolamine in a mass ratio of 12:1), 1.5 parts of polyether modified silicone oil, and 7 parts of water;
[0057] The preparation method is as follows:
[0058] According to the above-mentioned raw material ratios, titanium gypsum, blast furnace slag powder, hot-stewed converter steel slag powder, waste stone powder, composite cement, n-dodecane and n-decane are mixed in a mixer for 2 to 30 minutes until uniform; after aging for 32 hours, cold consolidation activator, polyether modified silicone oil and water are added thereto in sequence and mixed again for 2 to 6 minutes until uniform to obtain a mixture; the mixture is formed into spherical billets with a particle size of 0.125 to 9.5 mm by a ball-forming granulator; the spherical billets are first cured at a temperature of 25°C and a relative humidity of 92% for 1.5 days, and then cured in water at a temperature of 40°C for 10 days to obtain high-strength anti-icing lightweight aggregate.
[0059] After testing, the cylinder compressive strength of the high-strength anti-ice light aggregate obtained in this embodiment is 16.4MPa, and the apparent density is 1550kg / m 3 , the anti-freezing temperature is -22.3℃.
[0060] Example 4
[0061] The raw materials and amounts used in this example are as follows:
[0062] 85 parts of citric acid gypsum, 15 parts of blast furnace slag powder (particle size 65μm), 15 parts of hot-stewed converter slag powder (particle size 50μm), 30 parts of ceramic polishing waste (particle size 15μm), 6 parts of composite cement (compounded by ordinary Portland cement with strength grade 42.5 and sulphoaluminate cement with strength grade 52.5 in a mass ratio of 9:1), 0.8 parts of n-tetradecane, 1.2 parts of n-undecane, 2 parts of n-decane, 1.2 parts of cold consolidation activator (compounded by calcium chloride and triethanolamine in a mass ratio of 10:1), 2 parts of polyether modified silicone oil, and 5.5 parts of water;
[0063] The preparation method is as follows:
[0064] According to the above raw material proportions, citric acid gypsum, blast furnace slag powder, hot-stewed converter steel slag powder, ceramic polishing waste, composite cement, n-tetradecane and n-undecane are mixed in a mixer for 2 to 30 minutes until uniform; after aging for 46 hours, cold consolidation activator, polyether modified silicone oil and water are added thereto in sequence and mixed again for 2 to 6 minutes until uniform, to obtain a mixture; the mixture is formed into spherical billets with a particle size of 0.125 to 9.5 mm by a ball-forming granulator; the spherical billets are first cured at a temperature of 24°C and a relative humidity of 95% for 2 days, and then cured in a 10wt% sodium sulfate solution at a temperature of 30°C for 8 days to obtain high-strength anti-icing lightweight aggregate.
[0065] After testing, the cylinder compressive strength of the high-strength anti-ice light aggregate obtained in this embodiment is 11.7MPa, and the apparent density is 1430kg / m 3 , the anti-freezing temperature is -12.6℃.
[0066] Example 5
[0067] The raw materials and amounts used in this example are as follows:
[0068] 75 parts of citric acid gypsum, 20 parts of blast furnace slag powder (particle size 60μm), 10 parts of hot-stewed converter slag powder (particle size 60μm), 25 parts of silicon powder (particle size 15μm), 9 parts of composite cement (compounded by ordinary Portland cement with strength grade 42.5 and sulphoaluminate cement with strength grade 52.5 in a mass ratio of 10:1), 6 parts of n-tetradecane, 2 parts of n-undecane, 1.5 parts of polyether modified silicone oil, and 6 parts of water;
[0069] The preparation method is as follows:
[0070] According to the above raw material proportions, citric acid gypsum, blast furnace slag powder, hot-stewed converter steel slag powder, ceramic polishing waste, composite cement, n-tetradecane and n-undecane are mixed in a mixer for 2 to 30 minutes until uniform; after aging for 46 hours, cold consolidation activator, polyether modified silicone oil and water are added thereto in sequence and mixed again for 2 to 6 minutes until uniform to obtain a mixture; the mixture is formed into spherical billets with a particle size of 0.125 to 9.5 mm by a ball-forming granulator; the spherical billets are first cured at a temperature of 24°C and a relative humidity of 95% for 2 days, and then cured in an aqueous solution at a temperature of 30°C for 8 days to obtain high-strength anti-icing lightweight aggregate.
[0071] After testing, the cylinder compressive strength of the high-strength anti-ice light aggregate obtained in this embodiment is 17.2MPa, and the apparent density is 1615kg / m 3 , the anti-freezing temperature is -10.4℃.
[0072] Comparative Example 1
[0073] The difference from Example 1 is that the cold setting activator is 2.4 parts of calcium chloride; the rest is the same as Example 1.
[0074] After testing, the cylinder compressive strength of the high-strength anti-ice lightweight aggregate obtained in this embodiment is 14.8MPa, and the apparent density is 1632kg / m 3 , the anti-freezing temperature is -5.1℃.
[0075] Comparative Example 2
[0076] The difference from Example 1 is that the cold curing activator is 2.4 parts of triethanolamine; the rest is the same as Example 1.
[0077] After testing, the cylinder compressive strength of the high-strength anti-ice light aggregate obtained in this embodiment is 16.7MPa, and the apparent density is 1664kg / m 3 , the anti-freezing temperature is -4.5℃.
[0078] Comparative Example 3
[0079] The difference from Example 1 is that "15 parts of composite cement (compounded by ordinary Portland cement with strength grade 42.5 and sulphoaluminate cement with strength grade 52.5 in a mass ratio of 10:1)" is replaced with 15 parts of ordinary Portland cement with strength grade 42.5; the rest is the same as Example 1.
[0080] After testing, the cylinder compressive strength of the high-strength anti-ice lightweight aggregate obtained in this embodiment is 15.5MPa, and the apparent density is 1658kg / m 3 , the anti-freezing temperature is -6.1℃.
[0081] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0082] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A high-strength anti-ice lightweight aggregate, characterized in that: Including the following raw materials by mass: 50-90 parts of industrial by-product gypsum, 10-30 parts of slag, 5-15 parts of steel slag, 10-30 parts of ultra-fine nano powder, 2-15 parts of composite cement, 2-10 parts of anti-icing agent, 0.5-3 parts of cold solidification activator, 0.2-2 parts of polyether modified silicone oil and 12-30 parts of water.
2. The high-strength anti-icing lightweight aggregate according to claim 1, characterized in that: The industrial by-product gypsum includes one or more of desulfurized gypsum, phosphogypsum, titanium gypsum and citric acid gypsum; the attached water content of the industrial by-product gypsum is ≤20wt%, and the dry basis CaSO4·2H2O content is ≥80wt%; the slag includes blast furnace slag powder; the specific surface area of the slag is ≥400m 2 / kg, 28d intensity activity index ≥95%, particle size 0.1~75μm.
3. The high-strength anti-icing lightweight aggregate according to claim 2, characterized in that: The steel slag includes converter steel slag powder; the specific surface area of the steel slag is ≥530m 2 / kg, 28d strength activity index ≥80%, f-CaO content ≤2%, particle size 0.1-76μm; the ultra-fine nano powder includes one or more of fly ash, silica powder, waste stone powder, ceramic polishing waste; the specific surface area of the ultra-fine nano powder is ≥750m 2 / kg, average sphericity ≥0.85, particle size 0.1~38μm.
4. The high-strength anti-icing lightweight aggregate according to any one of claims 1 to 3, characterized in that: The composite cement is prepared by compounding silicate cement and sulphoaluminate cement, wherein the mass ratio of silicate cement to sulphoaluminate cement is 9-12:1; the strength grade of silicate cement is ≥42.5; and the strength grade of sulphoaluminate cement is ≥52.
5.
5. The high-strength anti-icing lightweight aggregate according to claim 1, characterized in that: The anti-icing agent includes two or more of n-tetradecane, n-dodecane, n-undecane and n-decane.
6. The high-strength anti-icing lightweight aggregate according to claim 1, characterized in that: The cold solidification activator is prepared by compounding calcium chloride and triethanolamine, and the mass ratio of calcium chloride to triethanolamine is 9 to 15:
1.
7. The method for preparing the high-strength anti-icing lightweight aggregate according to any one of claims 1 to 6, characterized in that: The steps include: According to the raw material ratio of the high-strength anti-icing lightweight aggregate, industrial by-product gypsum, slag, steel slag, ultrafine nano powder, composite cement and anti-icing agent are mixed and aged, and after the aging, cold solidification activator, polyether modified silicon and water are added in sequence and mixed and granulated to obtain spherical blanks; the spherical blanks are cured to obtain the high-strength anti-icing lightweight aggregate.
8. The method for preparing high-strength anti-icing lightweight aggregate according to claim 7, characterized in that: The mixing time is independently 2 to 30 minutes; the aging time is 24 to 48 hours.
9. The method for preparing high-strength anti-icing lightweight aggregate according to claim 7 or 8, characterized in that: The particle size of the spherical blank is 0.125-9.5 mm.
10. The method for preparing high-strength anti-icing lightweight aggregate according to claim 9, characterized in that: The curing includes a first curing and a second curing; the temperature of the first curing is 20-25°C, the relative humidity of the first curing is 90-98%, and the time of the first curing is 1-3 days; the second curing is curing in water or sodium sulfate solution, the temperature of the second curing is 20-40°C, and the time of the second curing is 7-14 days.
Citation Information
Patent Citations
Porous salt storage aggregate and preparation method thereof
CN101786834B
An anti-icing micro-surface treatment material and its preparation method
CN109534734B
Slow-release type anti-freezing polyurethane mixture suitable for steel bridge deck and preparation method of slow-release type anti-freezing polyurethane mixture
CN118026568A